Innovative outcome through exploration and exploitation: Enablers, barriers and industrial property - Nancy Vargas; M. Bego\~na Lloria; Addisson Salazar; Luis Vergara (European Journal of Management and Business Economics (EJM&BE), 2022)
Purpose - This research aims to study the effect of R&D (research and development) enablers and barriers as well as industrial property on exploration, their influence on exploitation and finally the possible impact on innovative outcome (IO) as a result variable. The IO can be defined as the orientation towards new or improved products, services and processes, as well as towards penetration and greater market share, which the company has obtained as a result of innovative processes. Design/methodology/approach - For this purpose, a new relationship model is defined, which is empirically contrasted in a quantitative study. We use a sample of large firms from different economic sectors with a high level of investment in R&D. Findings - The results indicate a close relationship between exploration and exploitation processes, as well as a positive impact on the innovative outcome. Moreover, the type of relationship that R&D enablers and barriers have with exploration is demonstrated and the lack of a positive effect of industrial property on exploration. Practical implications - These results may lead to new markets opening up and the creation or improvement of new products, services or processes in diverse sectors of highly innovative firms. Originality/value - This research aims to study the effect of R&D enablers and barriers and industrial property on learning flows and, finally, the possible impact on the innovative outcome. A new theoretical model of relationships is defined, and it is the first time that it is empirically tested.
Keywords: 650; Exploitation; Exploration; Industrial property; Innovative outcome; R&D enablers and barriers